ISO 50002 and ITS Contribution to the Decarbonization of SMES: Case Study - Ibarguen, Jenny; Castrillón, Rosaura (International Journal of Energy Economics and Policy, 2024)
The decarbonization of all sectors of the energy system is essential to mitigate climate change. However, the existing barriers, mainly related to information, prevent the implementation of Energy Efficiency measures and energy management systems in SMEs to reduce carbon emissions. An energy audit is considered a critical step for businesses that want to increase their energy efficiency and reduce energy consumption cost-effectively. The present study addressed ISO 50002 and its contribution to energy management based on the ISO 50001:2019 standard through a case study applied to an SME in the non-metallic mineral sector, which allowed establishing the guidelines and the form to address an energy audit in an SME under ISO 50002, determining opportunities for improvement by eliminating unproductive times, correcting fleeting compressed air, eliminating energy losses due to operational variability, automating the start-up of the Hammer Mill and the feed band in gypsum grinding. Additionally, an annual energy and economic savings potential of 162,599 KWh and COP 49,360,442 was estimated; and 26,992 Kg CO2 stopped emitting.